Saudi Arabia : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Saudi Arabia's real GDP growth is expected to increase to 1.9 percent in 2018, with non-oil growth strengthening to 2.3 percent. Growth is expected to pick-up further over the medium term as the reforms take hold and oil output increases. Risks are balanced in the near-term. The employment of Saudi nationals has increased, especially for women, but the unemployment rate among Saudi nationals rose to 12.8 percent in 2017. Credit and deposit growth remain weak, but both are expected to strengthen owing to higher government spending and non-oil growth. The fiscal deficit is projected to continue to narrow, from 9.3 percent of GDP in 2017 to 4.6 percent of GDP in 2018.